Mapping burned areas from Landsat TM/ETM+ data with a two-phase algorithm: Balancing omission and commission errors - Bastarrika, Aitor; Chuvieco, Emilio; Martín, M. Pilar (Remote sensing of environment, 2011)
Maps of burned area have been obtained from an automatic algorithm applied to a multitemporal series of Landsat TM/ETM+ images in two Mediterranean sites. The proposed algorithm is based on two phases: the first one intends to detect the more severely burned areas and minimize commission errors. The second phase improves burned patches delimitation using a hybrid contextual algorithm based on logistic regression analysis, and tries to minimize omission errors. The algorithm was calibrated using six study sites and it was validated for the whole territory of Portugal (89,000 km 2) and for Southern California (70,000 km 2). In the validation exercise, 65 TM/ETM+ scenes for Portugal and 35 for California were used, all from the 2003 fire season. A good agreement with the official burned area perimeters was shown, with kappa values close to 0.85 and low omission and commission errors (< 16.5%). The proposed algorithm could be operationally used for historical mapping of burned areas from Landsat images, as well as from future medium resolution sensors, providing they acquire images in two bands of the Short Wave Infrared (1.5–2.2 μm). ► Burned area maps were generated from automatic processing of Landsat TM/ETM+ images. ► Algorithm was applied to 65 TM/ETM+ scenes in Portugal and 35 in California. ► Kappa values were close to 0.85, with low omission and commission errors (< 16.5%).